The Authority of Majelis Tafsir Al-Qur'an (MTA) Fatwa: Critical Review of the MTA's Sunday Morning Brochure - Muh Nashirudin; Mudofir Mudofir (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2018)
This paper discusses the authority behind the Sunday Morning Brochure by Majelis Tafsir Al-Qurâ€™an (MTA). The Sunday Morning Brochure is a study material given on Sunday morning and distributed to MTA members, and they can be regarded as a fatwa or the result of the MTAâ€™s ijtihÄd in understanding the sources of Islamic law. From the documentations and interviews, this research finds that the study materials on the MTAâ€™s Sunday morning brochures have been designed by a team of experts under the supervision of Ahmad Sukina. However, the brochures are, in fact, only prepared individually by the chairman of the team, i.e. Masduki who cannot be said to be authoritative in the istinbÄá¹ or ijtihÄd of Islamic law because he does not meet the criteria as an individual mujtahid in establishing the Islamic law. While using the jargon back to the Qur'an and Sunnah, MTA still uses ijmÄ' and qiyÄs as a proposition though in a very limited case. Other sources than those four, such as istiá¸¥sÄn, maá¹£laá¸¥ah, and istiá¹£á¸¥Äb will not be used by the MTA.